Modulation of Plasma Proteomic Profile by Regular Training in Male and Female Basketball Players: A Preliminary Study - Militello, Rosamaria; Pinto, Gabriella; Illiano, Anna; Luti, Simone; Magherini, Francesca; Amoresano, Angela; Modesti, Pietro Amedeo; Modesti, Alessandra (Frontiers in Physiology, 2022)
Monitoring fatigue and recovery during training periods contributes to identifying the best training methods to achieve sports performance. To date, little is known about sex-related differences in sports adaptations. The aim of the present study is to identify sex-related sports adaptation proteins in female basketball players and male basketball players using proteomics approach on plasma samples withdrawn from athletes during in-season training period but far from a competition. A cohort of 20 professional basketball players, 10 female (BF) and 10 male (BM), and 20 sedentary male (10 CM) and female (10 CF) as control, of comparable age and BMI, were involved in this study. Protein profiles of plasma samples obtained from BM, BF, CM, and CF were analyzed by two-dimensional electrophoresis (2-DE). Differentially expressed proteins were identified by mass spectrometry. The computational 2-DE gel image analysis pointed out 33 differentially expressed protein spots (ANOVA p-value < 0.05) and differences between male and female basketball players are more evident among the players than controls. The expression profile of 54.5% of the total proteins is affected by sports activity. Furthermore, 14 proteins are differentially expressed in basket female players in comparison with their relative controls while seven are differentially expressed in basket male players in comparison with their controls. In conclusion, we identify in female athletes a reduction in proteins related to transcription regulation, most of these modulate chronic inflammation confirming the anti-inflammatory effect of regular training in female muscle metabolism. In male and female athletes, we found a decrease in Transthyretin involved in muscle homeostasis and regeneration and Dermcidin a stress-induced myokine linked to inflammatory and it will be interesting to fully understand the role of its different isoforms in male and female skeletal muscle contraction.